Repeatability and Reproducibility of Measurements Using a NT-530P Noncontact Tono/Pachymeter and Correlation of Central Corneal Thickness with Intraocular Pressure. (3rd October 2013) - Fujimura, Fusako; Kamiya, Kazutaka; Fujiwara, Kazuko; Shoji, Nobuyuki; Shimizu, Kimiya
Abstract : Purpose . To investigate the repeatability and reproducibility of intraocular pressure (IOP) and central corneal thickness (CCT) measurements using a noncontact tono/pachymeter (NT-530P) and to assess the correlation of CCT with IOP. Methods . Forty-six eyes of healthy volunteers were measured by two examiners. Three consecutive measurements per eye were performed. Repeatability was assessed using the coefficient of variation, and reproducibility was assessed using Bland-Altman plots. Linear correlations were used to determine agreement between CCT and noncorrected IOP and CCT and corrected IOP, which was calculated using a formula built into the NT-530P. Results . The coefficient of variation for IOP was 6.4% and for CCT was 0.4%. The 95% limits of agreement between examiners were − 0.17 ± 1.42 mmHg (range: − 2.95 to 2.61 mmHg) for IOP, − 0.93 ± 4.37 μ m (range: − 9.50 to 7.64 μ m) for CCT. The corrected IOP was significantly higher than the noncorrected IOP (P = 0.010.3 ). The noncorrected IOP significantly correlated with CCT (r = − 0.4883, P = 0.0006 ). The corrected IOP showed no significant correlation with CCT (r = − 0.0285, P = 0.8509 ). Conclusions . NT-530P offered repeatability and reproducibility in both IOP and CCT measurements. The corrected IOP calculated using the NT-530P was independent of the CCT, suggesting that this IOP may be less influenced by the central corneal thickness.